2022
DOI: 10.4102/sajpsychiatry.v28i0.1628
|View full text |Cite
|
Sign up to set email alerts
|

Mental illness and HIV amongst female inmates in Durban, South Africa

Abstract: Background: There is limited data regarding the prevalence of mental illness and human immunodeficiency virus (HIV) amongst female inmates in South Africa. Rehabilitation programmes can only be formulated once the needs of this population have been identified.Aim: This study aimed to measure the prevalence of mental illnesses, borderline and antisocial personality disorders and HIV amongst female inmates. Setting:The study was based at a correctional centre in Durban, KwaZulu-Natal, South Africa.Methods: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Mental disorders constitute the main area of investigation in the studies included in this review, represented by 17 single studies of which 7 are based on gender-mixed samples, see Table 2. Of the ten studies of mental disorders including female inmates only, one is from South Africa (Naidoo et al , 2022), three are from China (Zhong et al , 2021; Zhong et al , 2020; Zhu et al , 2017), three from the USA (Fogel & Martin, 1992; Harner et al , 2015; Jordan et al , 1996), two from Sweden (Edvinsson et al , 2010; Konstenius et al , 2015) and one from Germany (Rösler et al , 2009). The three studies from China, the one from South Africa, as well as one of the US studies (Jordan et al , 1996) investigated a broad spectrum of mental disorders, examined according to current diagnostic standards.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental disorders constitute the main area of investigation in the studies included in this review, represented by 17 single studies of which 7 are based on gender-mixed samples, see Table 2. Of the ten studies of mental disorders including female inmates only, one is from South Africa (Naidoo et al , 2022), three are from China (Zhong et al , 2021; Zhong et al , 2020; Zhu et al , 2017), three from the USA (Fogel & Martin, 1992; Harner et al , 2015; Jordan et al , 1996), two from Sweden (Edvinsson et al , 2010; Konstenius et al , 2015) and one from Germany (Rösler et al , 2009). The three studies from China, the one from South Africa, as well as one of the US studies (Jordan et al , 1996) investigated a broad spectrum of mental disorders, examined according to current diagnostic standards.…”
Section: Resultsmentioning
confidence: 99%
“…The three studies from China, the one from South Africa, as well as one of the US studies (Jordan et al , 1996) investigated a broad spectrum of mental disorders, examined according to current diagnostic standards. The prevalence of any current mental disorder varied from 26.1% (Zhong et al , 2020) (depression being the most prevalent), to 36.5% (Naidoo et al , 2022) (borderline personality disorder being the most prevalent), to 46.3% (Jordan et al , 1996) (drug and alcohol abuse being the most prevalent diagnostic categories). Zhu and coworkers (2017) report only on the overall prevalence of borderline personality disorder (10.6%).…”
Section: Resultsmentioning
confidence: 99%
“…The only study that focused on comorbidity between HIV and mental health problems 10 showed a high prevalence of mental illnesses among female inmates living with HIV. In particular, most (70.6%) of the female inmates with HIV reported depressive disorder, and nearly half reported alcohol use disorder (48.4%) and post-traumatic stress disorder (46.8%).…”
Section: Resultsmentioning
confidence: 99%
“…8 Also, the double stigma of being incarcerated and living with HIV has significant mental health implications. 9,10 Incarcerated persons often receive insufficient attention in their HIV care compared to PLHIV in the general population in Africa. 3 Additionally, guidelines and policies on HIV care are not routinely followed in prisons in Africa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation